Jefferson Scale of Lifelong Learning-Health Professions Students Version (JeffSLL-HPS): An Instrument to Measure Health Professions Students' Orientation Toward Lifelong Learning - Malorie Novak; Christie Palladino; Brittany Ange; Deborah Richardson (Association of American Medical Colleges, 2014)
Abstract The Jefferson Scale of Lifelong Learning - Health Professions Students (JeffSLL-HPS) is intended to measure health professions students' lifelong learning. The authors, with permission, modified the Jefferson Scale of Physician Lifelong Learning-Medical Students Version (JeffSPLL-MS) to assess orientation toward lifelong learning among students from a variety of health professions. The JeffSLL-HPS is a 14− item self-report questionnaire that may be administered on paper or electronically. The sum of the 14 items yields a total score with a range of 14-56. Higher JeffSLL-HPS scores indicate a greater orientation toward lifelong learning. Scores on the JeffSLL-HPS assess three factors: (1) learning beliefs and motivation, (2) attention to learning opportunities, and (3) technical skills in seeking information, consistent with scores on the JeffSPLL-MS. The JeffSLL-HPS may be valuable for faculty and administrators in health professions programs for assessing goals identified by accreditation standards and to assess the extent to which students value the importance of lifelong learning throughout their careers. The assessment tool and guidelines for usage are included as downloadable files. The authors electronically administered the JeffSLL-HPS to 502 senior health professions students in eight programs at GRU. One-hundred and eighty (35.9%) respondents returned complete surveys. Our work with the JeffSLL-HPS demonstrates internal structure of responses consistent with that of the JeffSPLL-MS1 and suggests that the JeffSLL-HPS may be used as a reliable method of assessing orientation to lifelong learning in students from multiple healthcare disciplines. To date, we have only tested the JeffSLL-HPS at our institution. We are conducting longitudinal research with the instrument to study if students' orientation toward lifelong learning changes over time.